2009
DOI: 10.1002/bdrb.20190
|View full text |Cite
|
Sign up to set email alerts
|

Embryo/fetal development in cynomolgus monkeys exposed to natalizumab, an α4 integrin inhibitor

Abstract: Natalizumab had no abortifacient or teratogenic effects, but was associated with changes in fetal hematopoiesis and leukocyte trafficking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 32 publications
2
37
2
1
Order By: Relevance
“…Studies of natalizumab in MS have shown reduced relapse rates and disability progression, but less is known about its effects on pregnancy outcomes [10, 11]. Natalizumab is classified as a pregnancy category C drug, as potential fetal effects have been reported in animal studies [1214] and there is a paucity of well-controlled human studies [6]. Although some animal studies have shown that natalizumab can cross the placental barrier and produce hematologic effects on fetal guinea pigs and primates [6, 12, 14, 15], others have not shown fetal interaction [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of natalizumab in MS have shown reduced relapse rates and disability progression, but less is known about its effects on pregnancy outcomes [10, 11]. Natalizumab is classified as a pregnancy category C drug, as potential fetal effects have been reported in animal studies [1214] and there is a paucity of well-controlled human studies [6]. Although some animal studies have shown that natalizumab can cross the placental barrier and produce hematologic effects on fetal guinea pigs and primates [6, 12, 14, 15], others have not shown fetal interaction [16].…”
Section: Introductionmentioning
confidence: 99%
“…Natalizumab is classified as a pregnancy category C drug, as potential fetal effects have been reported in animal studies [1214] and there is a paucity of well-controlled human studies [6]. Although some animal studies have shown that natalizumab can cross the placental barrier and produce hematologic effects on fetal guinea pigs and primates [6, 12, 14, 15], others have not shown fetal interaction [16]. Human studies and case reports have not shown increases in spontaneous abortions or birth defects; however, results are limited by small sample sizes [17–20].…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate any potential effects of ustekinumab treatment during pregnancy, it was necessary to conduct developmental studies in cynomolgus macaques. The cynomolgus macaque is a species frequently used for the non-clinical safety evaluation of human therapeutic monoclonal antibodies (Chellman et al, 2009;Martin, 2008;Martin et al, 2007Martin et al, , 2009Wehner et al, 2009). The cynomolgus macaque is physiologically and endocrinologically similar to humans (Chellman et al, 2009;Weinbauer et al, 2008a,b).…”
Section: Introductionmentioning
confidence: 99%
“…However, in preclinical studies, no cardiac abnormalities were reported in monkeys treated with doses up to 30 mg/kg. 14 Information on pregnancy outcomes is limited. In the natalizumab MS and Crohn's disease clinical trial program, 41 pregnancies were reported.…”
Section: Natalizumabmentioning
confidence: 99%